Shelf Life Date Extension of Fresh-Cut Salad: A Consumer Perspective. Issue 8 (17th November 2017) - Stranieri, Stefanella; Baldi, Lucia
ABSTRACT: During the past decades, various technological applications relating to an extension of the shelf life of food products have been introduced. The adoption of such technologies in the fresh-cut salad sector is a key issue for the sustainable management of the supply chain. The aim of the study is to analyse consumers' attitude towards fresh-cut salad with an extended shelf life date. The analysis was based on face-to-face interviews with 351 consumers living in Lombardy, one of the Italian provinces where the consumption of fresh-cut salad is high and characterized by good margins of development. Principal component factor analysis with varimax rotation was used as preliminary data preparation for market segmentation. Cluster analysis revealed the presence of three different consumers groups. Only the cluster of 'favorable' shows a positive attitude towards the extended shelf life date. Consumers grouped in the cluster of 'skeptical' associate such innovation to a low level of product freshness. The cluster of 'mistrust' reveals the presence of consumers with safety concerns towards the prolongation of the shelf life date. Such consumers do not reveal a high level of trust in processing firms and their related brands.